The CB2 Cannabinoid System: A New Strategy in Neurodegenerative Disorder and Neuroinflammation - Marialessandra Contino (Frontiers Research Topics, 2017)
The neurodegenerative disorders such as Parkinson's disease (PD) or Alzheimer's disease (AD) are the most common forms of dementia and no pharmacological treatments are to date available for these diseases. Indeed, the only used drugs are symptomatic and no useful to block the progression of the diseases. The lack of a therapeutic approach is also due to a lack of an early diagnosis. This Research Topic describes a new target that is involved in the firs step of these disorders and that can be useful for the treatment and the diagnosis of such pathologies: the cannabinoid receptor subtype 2 or CB2R. Indeed, CB2R is overexpressed in reactive microglia and activated astrocytes during neuroinflammation and thus their detection by PET probes can be an easily strategy for an early diagnosis of neurodegeneration. Moreover, CB2 agonists and inverse agonists displayed neuroprotective effects and they so can be candidated as new therapeutich drugs for the treatment of these pathologies. Therefore, the aim of this Research Topic is to show the great potential of CB2R ligands for the development of new tools/drugs for both the therapy and the diagnosis of neurodegeneration.